ANALISIS DPSIR (DRIVER, PRESSURE, STATE, IMPACT, DAN RESPONSE) HUTAN MANGROVE DI SULAWESI SELATAN: STUDI KASUS DI KABUPATEN TAKALAR - Abdul Malik; Abdul Rahim; Abdul Jalil Rasyid; Abdul Mannan; Dary Setiawan Arif (Jurnal Environmental Science, 2023)
Degradation and deforestation of mangrove forests in South Sulawesi continues due to high dependence and unsustainable use of mangrove ecosystem services. Therefore, considering decisions in efforts to protect and sustainably manage mangrove forests is needed. This research aims to formulate policies related to the protection and sustainable management of mangroves due to the degradation and deforestation of mangrove forests in South Sulawesi using the DPSIR (Driver, Pressure, State, Impacts, and Response) approach, with a case study of the Takalar Regency mangrove forest. Data collection includes secondary and primary data, which includes field observations and interviews with questionnaires to local communities (150 respondents) using purposive sampling. Moreover, semi-structured interviews were conducted with local governments (1 respondent), Non-Governmental Organizations (NGOs) (1 respondent), and mangrove experts from university (2 respondents) and then tabulated and analyzed using the DPSIR approach. The results show that several policy recommendations that can be considered in reducing pressure, improving the condition of mangrove forests, and reducing the impacts, are as follows: (1) carrying out mangrove rehabilitation and restoration efforts, (2) establishing natural conservation zones and green belts, (3) implementing sustainable mangrove utilization practices and developing integrative management plans (4) increasing community participation, knowledge, and access to education, (5) creating alternative forms of employment, (6) increasing awareness about the need to carry out assessments regarding the economic benefits of mangroves, (7) encouraging the development of payment schemes for ecosystem services, (8) developing and implementing an environmentally friendly integrated mangrove cultivation system (silvo-fishery model), (9) establishing a policy and legislative framework for the protection and management of mangroves, (10) ensuring legal certainty and enforcement, (11) eliminating all existing and ongoing forms of subsidies or incentives that can cause degradation or loss of mangroves, and (12) supporting and encouraging the development of mangrove ecotourism.Keywords: DPSIR, Mangrove Forests, Deforestation, Sustainable Management, South Sulawesi